UJIAN SERTIFIKASI AKUNTAN PUBLIK: DETERMINAN, POLA KELULUSAN, DAN EVALUASI UJIAN - Gani, Lindawati; Leo, Lianny (Jurnal Akuntansi dan Keuangan Indonesia, 2009)
This study analyzes determinants of passing the Indonesia CPA exam, whether there is any pattern ofpassing the exam, and the validity and reliability of tests. The analysis shows that sex (gender) and accounting education systems do not determine the odd ofpassing the CPA exam, however the probability to pass the exam is higher for younger test-takers and those working in public accounting firms. We also obtain the evidence of a significant pattern of passing the exam. The probability of exam takers passing in the first sitting of each subject apparently approximates the probability of test-takers passing the CPA exam. There is a diminishing probability of passing the exam as exam takers repeat. Result indicates a consistent order of passing rate shown by each subject. Audit, Financial Management- Management Accounting, and Accounting Information System are the subjects which share consistent highest passing rates, followed by Financial Accounting and Tax-Law, which show the lowest passing rate. Except for Financial Management-Management Accounting, the sampled test items do not meet the minimum scores of validity and reliability. We suggest that future research include a qualitative analysis on test items and that pre-test is conducted before test items are included in the data bank.